Use of qualitative behavioural assessment to investigate affective states of housed dairy cows under different environmental conditions - Russell, Alison L.; Randall, Laura V.; Kaler, Jasmeet; Eyre, Nikki; Green, Martin J. (Frontiers in Veterinary Science, 2023)
In addition to the reduction of suboptimal welfare, there is now a need to provide farmed animals with positive opportunities to provide confidence that they have experienced a life worth living. Diversification of the environment through environmental enrichment strategies is one suggested avenue for providing animals with opportunities for positive experiences. The provision of more stimulating environmental conditions has been widely implemented in other animal production industries, based on evidenced welfare benefits. However, the implementation of enrichment on dairy farms is limited (29). In addition to this, the relationship between enrichment and dairy cows’ affective states is an under-researched area. One specific welfare benefit of enrichment strategies which has been observed in a number of species, is increased affective wellbeing. This study investigated whether the provision of different forms of environmental enrichment resources would impact the affective states of housed dairy cows. This was measured by Qualitative Behavioural Assessment, currently a promising positive welfare indicator. Two groups of cows experienced three treatment periods; i) access to an indoor novel object, ii) access to an outdoor concrete yard and iii) simultaneous access to both resources. Principal component analysis was used to analyse qualitative behavioural assessment scores, which yielded two principal components. The first principal component was most positively associated with the terms ‘content/relaxed/positively occupied’ and had the most negative associations with the terms ‘fearful/bored’. A second principal component was most positively associated with the terms ‘lively/inquisitive/playful’ and was most negatively associated with the terms ‘apathetic/bored’. Treatment period had a significant effect on both principal components, with cows being assessed as more content, relaxed and positively occupied and less fearful and bored, during periods of access to additional environmental resources. Similarly, cows were scored as livelier, more inquisitive and less bored and apathetic, during treatment periods compared to standard housing conditions. Concurrent with research in other species, these results suggest that the provision of additional environmental resources facilitates positive experiences and therefore enhanced affective states for housed dairy cows.